2022
DOI: 10.1016/j.virs.2022.01.029
|View full text |Cite
|
Sign up to set email alerts
|

The mutational dynamics of the SARS-CoV-2 virus in serial passages in vitro

Abstract: Since its outbreak in 2019, Severe Acute Respiratory Syndrome Coronavirus 2 keeps surprising the medical community by evolving diverse immune escape mutations in a rapid and effective manner. To gain deeper insight into mutation frequency and dynamics, we isolated ten ancestral strains of SARS-CoV-2 and performed consecutive serial incubation in ten replications in a suitable and common cell line and subsequently analysed them using RT-qPCR and whole genome sequencing. Along those lines we hoped to gain fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This observation is consistent with findings from previous studies, in which mutational adaptive changes are usually not recorded until after at least four passages in vitro. This phenomenon has been described for RNA viruses [ 18 , 19 ], as well as some DNA viruses, including poxviruses, such as Fowlpox virus [ 20 ]…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with findings from previous studies, in which mutational adaptive changes are usually not recorded until after at least four passages in vitro. This phenomenon has been described for RNA viruses [ 18 , 19 ], as well as some DNA viruses, including poxviruses, such as Fowlpox virus [ 20 ]…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, several studies have assessed the genomic behaviour of viruses maintained in cultures, especially RNA viruses. Some of these studies have revealed adaptive changes after serial viral passages in vitro, but none earlier than four passages [ 18 , 19 ]. Others have entirely failed to document differences at a genomic level when comparing viruses from directly collected samples and in-vitro grown viruses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RNAs we sequenced originate mainly from cell lysates but may also contain portions of extracellular virions. Another aspect is the occurrence of subpopulations in vivo and in vitro , so-called quasi-species [53], which, as explained in the previous section, can influence the results. In addition, the RNA was prepared after the occurrence of a cytopathic effect detectable by light microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, mutations involved in SARS-CoV-2 entry into cells were evolved by serial passage in human cell lines without ACE2 or cellular proteases 22, 29 . Furthermore, several mutations reported in natural variants were recapitulated by serial passaging in several human cell lines, with some differences between colon epithelial cells and lung epithelial cells 30 .…”
Section: Discussionmentioning
confidence: 99%